Islamic Defense Action Movement 212 in the Perspective of Muslim - Katimin Katimin; Tumpal Panggabean (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
In quantity, Indonesia has the biggest Muslim in the word. However, the history is a proof that political identity labeled Islam has never succeeded in Indonesian presidential election. This is inseparable from the friction among Muslims who are divided when they come into contact with the territory. Besides, the purity of Islam, especially in the eyes of the laity, seems tarnished if Islam is associated with political attachments. This term is deliberately raised by certain stakeholders to win the public domain since Indonesia is democracy system. The presence of the Islamic defense action 212 was able to catch an eye of the public at large when the divided Muslims have one common enemy (blasphemy of the al-Qur'an). This phenomenon gives a large political power as a rival for the incumbent. This is qualitative research with literature study method and analysis of the phenomenology of Islamic defense action 212. The reference taken is closely related to the information media that describes the public discourse about Ahok's defamation of the Quran to various sustainable Islamic defense action movements. The results of the research show that the 212 movement is neither a political movement nor Islamic mass organization but is a calling of the Muslim community in Indonesia who feels that their religion has been tarnished in the context of defamation of the holy verse of the Qur'an. Furthermore, Islamic defense action 212 establishes not only a political map in Indonesia but also other dimensions in the form of a Muslim-based business spirit such as the Muslim entrepreneurial center (212 mart). Koperasi Syariah 212 was supported by community figures, and the forerunner of the establishment of Islamic banking system in Indonesia.